PHYSIOTHERAPY MANAGEMENT IN BELL'S PALSY CASE WITH ELECTRICAL STIMULATION AND MASSAGE MODALITIES: A CASE REPORT - Aryanti, Widya; Sudaryanto, Wahyu Tri (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Bell's Palsy is a condition where there is facial paralysis resulting in paralysis of the peripheral facial nerve acute and currently the cause is unknown (idiopathic) in the absence of other neurologic abnormalities. The goal to be achieved is to know the benefits of Electrical Stimulation and Mirror Exercise in the case of Bell's Palsy (BP). Case Presentation: A 50-year-old woman presented with left-sided facial paralysis and asymmetry. The patient received therapy 6 times with Electrical Stimulation and Mirror Exercise modalities. Management and Outcome: : Patient follows 6 times therapy in 1 week 2 times meeting, in 1 time therapy for 30 minutes which is given Electrical Stimulation modality for 15 minutes and Massage for 15 minutes. Muscle strength was measured using MMT (Manual Muscle Testing), and for facial functional ability using Ugo fisch. Discussion: The results obtained after doing therapy 6 times using Electrical Stimulation and Massage are an increase in muscle strength, and facial functional abilities M. Frontalis T0: 1 to T6:5 , M. Corugator supercili T0:1 to T6:5, M. Procerus T0:5 to T6:5, M.Orbicularis Oculi T0:1 to T6:3, M. Nasalis T0:1 to T6:5, , M.Zygomaticus Major & minor T0:1 to T6:5, M. Orbicularis Oris T0:1 becomes T6:3, M. Bucinator T0:5 becomes T6:5, M.Mentalis T0:5 becomes T6:5. Conclusion: Management of Physiotherapy in the case of Bell's Palsy using an exercise program for 6 times therapy with Electrical Stimulation and Mirror Exercise modalities can be an intervention that can be done in overcoming the problem of Bell's Palsy.